PENERAPAN UNSUR DAN PRINSIP DESAIN BERDASARKANSUMBER IDE KARAKTERISTIK WAYANG WADON PADA BUSANA PESTA - Purwosiwi Pandansari sari; Nailal Khusna (SINERGI : Jurnal Riset Ilmiah, 2026)
This research aims to analyze and apply the elements and principles of fashion design inspired by the characteristics of wayang wadon in party dresses. Wayang wadon, as an element of traditional Javanese culture, possesses rich visual and symbolic characteristics, full of artistic and philosophical values. This study uses a qualitative approach with an exploratory-descriptive method to identify the visual elements of wayang wadon that can be adapted into modern fashion design. Elements such as lines, shapes, colors, and textures are explored and integrated with design principles such as balance, proportion, harmony, and rhythm. The results of the research show that the combination of traditional wayang wadon elements with modern fashion design produces clothing that is not only aesthetic but also has deep cultural value. Additionally, this research is expected to contribute to the development of fashion design that elevates local cultural values and enhances appreciation for Indonesian traditional art in the context of contemporary fashion.